Selectivity of herbicides applied in density cotton crop. = Seletividade de herbicidas aplicados na cultura do algodão adensado. - Cleiton Lopes da Silva; Miriam Hiroko Inoue; Kassio Ferreira Mendes; Cassiano Luiz Sztoltz; Breno Araguaia Souza Silva; Paulo Alberto Conciani (Agro@mbiente On-line, 2013)
Weed reduce yield and quality of cotton fiber, because this culture has slow growth in the early stages of its cycle. Thus, the objective of this present work to evaluate weed control and selectivity of herbicides applied pre- and post-emergence, in density cotton. Ten treatments with herbicides fomesafen, clomazone, diuron, prometryne, trifloxysulfuron-sodium, pyrithiobac-sodium, S-metolachlor and fluazifop-butyl, applied in mixture or sequential, and a control without herbicide were evaluated. The experiments were performed simultaneously with the same treatments in district of Deciolândia, municipality of Diamantino - MT, with a variety Fabermax 966 and in municipality of Sapezal - MT, with a variety DP 604. During thedevelopment of culture, phytointoxication and control levels at 7, 14 and 28 days after application (DAA); stand and height at 28 DAA; number of apples at 145 DAA and productivity of cotton in seed at 160 DAA were evaluated. Independent of the varieties of cotton, all treatments caused phytointoxication early, only treatments 4, 5 and 6 of experiment 1 did not differ from the control in productivity, but the other did not affect productivity, stand, plant height, number of bolls, and provide effective control of weeds, being selective in cotton. The mixture fomesafen + prometryne applied in pre-emergence, was also selective varieties of cotton Fabermax 966 and DP 604, however fomesafen is not registered for the crop. = As plantas daninhas reduzem a produtividade e a qualidade da fibra do algodoeiro, pelo fato desta cultura apresentar crescimento lento nos primeiros estádios de seu ciclo. Assim, objetivou-se com o presente trabalho avaliar o controle de plantas daninhas e a seletividade de herbicidas, aplicados em pré e em pós-emergência, no algodão adensado. Foram testados 10 tratamentos com os herbicidas fomesafen, clomazone, diuron, prometryne, trifloxysulfuron-sodium, pyrithiobac-sodium, S-metolachlor e fluazifop-butil, aplicados em mistura ou sequencial, além da testemunha sem aplicação de herbicida. Osexperimentos foram realizados simultaneamente com os mesmos tratamentos, no distrito de Deciolândia, município de Diamantino - MT, com a variedade Fabermax 966 e no município de Sapezal - MT, com a variedade DP 604. Durante o desenvolvimento da cultura, foram realizadas avaliações de fitointoxicação e níveis de controle aos 7, 14 e 28 dias após a aplicação (DAA); estande e altura aos 28 DAA; número de maçãs aos 145 DAA e produtividade do algodão em caroço aos160 DAA. Independentes das variedades de algodoeiro, todos os tratamentos avaliados causaram fitointoxicações iniciais,apenas os tratamentos 4, 5 e 6 do experimento 1 não diferiram da testemunha na produtividade, porém os demais não afetaramnegativamente a produtividade, estande, altura de plantas, número de maçãs, além de proporcionar controle efetivo de plantas daninhas, sendo seletivos ao algodoeiro. A mistura fomesafen + prometryne aplicada em pré-emergência, foi seletiva as variedades de algodoeiro Fabermax 966 e DP 604, entretanto o fomesafen não é registrado para a cultura.